2010
DOI: 10.1186/1744-859x-9-23
|View full text |Cite
|
Sign up to set email alerts
|

The opposite effects of fluvoxamine and sertraline in the treatment of psychotic major depression: a case report

Abstract: BackgroundPsychotic major depression is a clinical subtype of major depressive disorder. A number of clinical studies have demonstrated the efficacy of the combination of an antidepressant (for example, a tricyclic antidepressant or selective serotonin reuptake inhibitor (SSRI)) and an atypical antipsychotic or electroconvulsive therapy (ECT) in treating psychotic major depression. In several studies, monotherapy of SSRIs such as fluvoxamine has been shown to be effective in the treatment of psychotic major de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…The efficacy results of this study are consistent with other studies using the same drug in populations from Europe and other regions [19] [26]- [28]. The observed 75% reduction in the HAMD-17 score with fluvoxamine treatment is similar to the clinically significant change of 71% recorded in another study [29].…”
Section: Discussionsupporting
confidence: 91%
“…The efficacy results of this study are consistent with other studies using the same drug in populations from Europe and other regions [19] [26]- [28]. The observed 75% reduction in the HAMD-17 score with fluvoxamine treatment is similar to the clinically significant change of 71% recorded in another study [29].…”
Section: Discussionsupporting
confidence: 91%
“…Fluvoxamine abolished delusions, while sertraline was devoid of effect on this symptom. The authors attributed the efficacy of fluvoxamine on delusions to its σ 1 -agonist activity (56). Since the clinical dose of fluvoxamine was two times higher than the sertraline dose, whereas the fluvoxamine affinity for σ 1 -site is also two times higher, it may therefore be suggested that sertraline did not interact with the σ 1 -sites at its clinically active dose, contrarily to fluvoxamine, explaining its lack of effect on delusions.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are coherent with the reports of Bergeron et al (31) and Rogoz and Skuza (54). Interestingly, several recent reports (35,55,56) demonstrated, on neurite sprouting in PC12 cells and from human clinical studies, that fluvoxamine's action involve a σ 1 -agonist effect in its pharmacological activity, while sertraline was devoid of effect or showed opposite effects. The effects observed with sertraline could in fact appear coherent with an "inverse agonist" activity at σ 1 -sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggest that the interaction between brain 5‐HT 1A and σ 1 receptors is involved in the amelioration of the depressive‐like state observed in picrotoxin‐treated mice. The effectiveness of SSRIs with an affinity for the σ 1 receptor has also been shown in a number of clinical studies (Carrasco and Sandner, ; Kishimoto et al, ). Taken together with the recent finding that fluvoxamine increases prefrontal dopamine release in picrotoxin‐treated mice and that the effect is mediated by co‐activation of the 5‐HT 1A and σ 1 receptors (Ago et al, ), it is likely that the increased prefrontal dopamine release results in an anti‐anhedonic effect.…”
Section: Discussionmentioning
confidence: 79%